Effect of short glass fiber/filler particle proportion on flexural and diametral tensile strength of a novel fiber-reinforced composite. Issue 1 (January 2016) - Fonseca, Rodrigo Borges; de Almeida, Letícia Nunes; Mendes, Gustavo Adolfo Martins; Kasuya, Amanda Vessoni Barbosa; Favarão, Isabella Negro; de Paula, Marcella Silva
Abstract: Purpose: To evaluate the effect of glass fiber/filler particles proportion on flexural strength and diametral tensile strength of an experimental fiber-reinforced composite. Methods: Four experimental groups ( N  = 10) were created using an experimental short fiber-reinforced composite, having as a factor under study the glass fiber (F) and filler particle (P) proportion: F22.5/P55 with 22.5 wt% of fiber and 55 wt% of filler particles; F25/P52.5 with 25 wt% of fiber and 52.5 wt% of filler particles; F27.5/P50 with 27.5 wt% of fiber and 50 wt% of filler particles; F30/P47.5 with 30 wt% of fiber and 47.5 wt% of filler particles. The experimental composite was made up by a methacrylate-based resin (50% Bis-GMA and 50% TEGDMA). Specimens were prepared for Flexural Strength (FS) (25 mm × 2 mm × 2 mm) and for Diametral Tensile Strength (DTS) (3 × 6 Ø mm) and tested at 0.5 mm/min in a universal testing machine. Results: The results (in MPa) showed significance (different superscript letters mean statistical significant difference) for FS ( p  < 0.009) and DTS ( p  < 0.001) – FS results: F22.5/P55: 217.24 ± 20.64 B ; F25/P52.5: 245.77 ± 26.80 AB ; F27.5/P50: 246.88 ± 32.28 AB ; F30/P47.5: 259.91 ± 26.01 A . DTS results: F22.5/P55: 21.82 ± 4.42 B ; F25/P52.5: 22.00 ± 7.40 B ; F27.5/P50: 18.63 ± 4.41 B ; F30/P47.5: 31.05 ± 2.97 A . In SEM analysis, areas without fiber reinforcement demonstrated to be more prone to the presence of bubbles and crack development. The group F30/P47.5 showed areas with a great quantity of fibers without empty spaces for crack propagation. Conclusion: Increasing fiber content results in higher flexural and diametral tensile strength of an experimental composite reinforced with glass fibers.